THE IMPORTANCE OF TEACHING METHODS OF NATURAL SCIENCE IN ELEMENTARY GRADES - Elmuradova Inoyat Abdumutalipovna (Journals Park Publishing, 2022)
Natural science is a subject that gives schoolchildren a general understanding of the whole being, and it is important to teach this subject to elementary school students on the basis of various interesting games and using effective teaching methods. The methodology of teaching natural science allows to study the development of natural phenomena in connection with each other. The article talks about the importance of teaching natural science in primary grades.
Keywords: natural science, methodology of teaching natural science, pedagogical science, research methods.